1998
DOI: 10.1103/physrevc.57.941
|View full text |Cite
|
Sign up to set email alerts
|

Structure analysis of the virtual Compton scattering amplitude at low energies

Abstract: We analyze virtual Compton scattering off the nucleon at low energies in a covariant, model-independent formalism. We define a set of invariant functions which, once the irregular nucleon pole terms have been subtracted in a gauge-invariant fashion, is free of poles and kinematical zeros. The covariant treatment naturally allows one to implement the constraints due to Lorentz and gauge invariance, crossing symmetry, and the discrete symmetries. In particular, when applied to the ep → e ′ p ′ γ reaction, charge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
235
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(243 citation statements)
references
References 25 publications
(122 reference statements)
6
235
0
Order By: Relevance
“…[Gui95] by the introduction of mixed multipoles which were neither electric nor longitudinal. However the findings of a recent work [Dre98] allow for a much more elegant solution.…”
Section: Low Energy Behaviour and Generalized Polarizabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[Gui95] by the introduction of mixed multipoles which were neither electric nor longitudinal. However the findings of a recent work [Dre98] allow for a much more elegant solution.…”
Section: Low Energy Behaviour and Generalized Polarizabilitiesmentioning
confidence: 99%
“…In Ref. [Dre98] it has been shown that P (11,00)1 is not independent and can be eliminated according to …”
Section: Low Energy Behaviour and Generalized Polarizabilitiesmentioning
confidence: 99%
“…That this is not a model-dependent statement could be shown in [14], where the reduction from three to two polarizabilities was traced back to a combination of invariance with respect to charge conjugation and nucleon crossing. A similar reduction from seven to four terms occurs for the spin-dependent polarizabilities.…”
Section: The Rare Decay η → ππγγ In Chiral Perturbation Theorymentioning
confidence: 99%
“…The corresponding ten GPs, P (01,01)0 , ...,P (11,2)1 , are functions of |q| 2 , where mixed-type polarizabilities,P (ρ L ,L)S (|q| 2 ), have been introduced which are neither purely electric nor purely Coulomb type (see [8] for details). Only six of the above ten GPs are independent, if chargeconjugation symmetry is imposed [11,12]. For example, for a charged pion, the constraint for the Compton tensor reads [10,11] M µν π…”
Section: Generalized Polarizabilitiesmentioning
confidence: 99%
“…Relations between the GPs at |q| = 0 and the four spin-dependent RCS polarizabilities γ i of Ref. [20] were discussed in [12]:…”
Section: Generalized Polarizabilitiesmentioning
confidence: 99%